Prevention of Non-Communicable Diseases Education By Monitoring Nutritional Status and Balanced Nutritional Patterns In Students and Migrant Workers in Saudi Arabia - Muwakhidah; Hidayati, Listyani; Sintowati, Retno; Adelia Triana Putri; Siti Mulyati; Aulia Setyaningsih; Maulida Khotimah; Farisin Hanif Luthfilhadi; Muhammad Nabil Miqdam; Khayla Febriannisa; Rizkia Nur Ramadhani (Universitas Muhammadiyah Surakarta, 2025)
Hypertension and diabetes mellitus are among the most prevalent non-communicable diseases (NCDs) worldwide, strongly influenced by dietary patterns and environmental factors. The prevalence of these conditions in Saudi Arabia remains notably high. Preventive efforts are essential and can be strengthened through routine anthropometric and biochemical monitoring, alongside education on balanced and healthy diets. A substantial number of Indonesian citizens particularly migrant workers and students reside in Saudi Arabia, making early NCD prevention crucial for sustaining their long-term health and productivity. This community service program aimed to improve the knowledge and awareness of Indonesian workers and students in Saudi Arabia regarding NCD prevention. The activities included anthropometric assessments, biochemical examinations, and educational sessions on infectious diseases and associated risk factors. The program was conducted in collaboration with PCIM Saudi Arabia and study groups consisting of mothers and students in Mecca. A total of 11 sessions were held in both online and offline formats. The webinar series comprised five sessions featuring speakers from PCIM, PPMI, and the PKMKI Team, and attracted 87 participants, including UMS students, university students, and migrant workers in Saudi Arabia. Pre- and post-test results demonstrated a significant improvement in participants’ knowledge following the webinars. Participants showed high enthusiasm, despite sessions being scheduled in the evening. This program is expected to enhance awareness among students and migrant workers about the importance of monitoring their nutritional status and maintaining a healthy diet as key strategies for preventing non-communicable.